Impacts of in vitro salt stress microtuber production of Bintje and Eigenheimer potato cultivars - Kamil, Yaseen Sabah; Abdulhussien, Muslim Abd Ali; Ali, Abdulminam Hussien (Journal of Kerbala for Agricultural Sciences, 2016)
This study was conducted at the plant tissue culture lab. located at the department of horticulture and landscape gardening ∕ college of agriculture ∕ university of Kufa. Effect of salinity stress on the production of microtubers and there quality characters using different concentrations of sodium chloride 0, 50, 100, 150 mM added to MS medium provided with 5 mg . L-1 BA, 1 mg . L-1 thiamine, 0.5 mg . L-1 pyridoxine, 100 mg . L-1 nicotinic acid, 100 mg . L-1 Myo- inositol, 80 g . L-1 sucrose and 7 g . L-1 agar which specialized in microtuber production was achieved. Results showed that the addition of 50 mM of sodium chloride increased the number and diameter of micro- tuber to( 2.49, 3.31) mm respectively, while the content of micro- tuber of proline and total soluble sugars was increased when the medium modified to 150 mM of sodium chloride. The results also revealed a significant increase in qualitative and quantitative characteristic rate of Eigenheimer verity, meanwhile the Bintje verity gave the highest rate of microtuber diameter. Interaction between verity and salinity concentration were significantly affected the micro-tuber growth indicators and its content of proline and soluble sugar, where the Eigenheimer verity and the concentration 50 Mm get the highest rate of micro-tuber number (2.66) and the highest amount of proline and total soluble sugar(0.877, 0.277) mg.g-1 respectively, with the concentration of 150 Mm . Depending on phonotypical indicators and cell content and organic soluble of proline and soluble sugar could conclusion that Eigenheimer verity was the most tolerant to the salinity stress than Bintje verity.